Prevalence of infectious diseases in patients with autoimmune blistering diseases. Issue 4 (11th February 2020) - Ujiie, Inkin; Ujiie, Hideyuki; Yoshimoto, Norihiro; Iwata, Hiroaki; Shimizu, Hiroshi
Abstract: A long‐term immunosuppressive treatment can provoke latent infections. Autoimmune blistering diseases (AIBD) are mostly treated with systemic immunosuppressive agents. To prevent the reactivation or exacerbation of existing latent infections, patients must be screened for infectious diseases before immunosuppressive treatments are initiated. However, the prevalence of infectious diseases in AIBD remains to be elucidated. To evaluate the necessity of screening infectious diseases in AIBD, we retrospectively reviewed the clinical records of 215 patients at a single center with AIBD for hepatitis B virus (HBV), hepatitis C virus (HCV), Mycobacterium tuberculosis, Treponema pallidum, human T‐cell leukemia virus type 1 (HTLV‐1) and HIV infections. Approximately 40% of patients were infected with HBV. During systemic corticosteroid treatment, HBV DNA became positive in 3.4% of cases. Antibodies to HCV, interferon‐γ release assays for M. tuberculosis and the T. pallidum latex agglutination test were positive in 0.6%, 6.6% and 1.2% cases, respectively. Neither HTLV‐1 nor HIV infections were detected. In conclusion, checks for HBV and M. tuberculosis infections should be made before immunosuppressive treatments are started, because of the high prevalence of these potentially life‐threatening infections. Other infections should be tested for depending on the patient's risk factors.